A reversed gender pattern? A meta-analysis of gender differences in the prevalence of non-suicidal self-injurious behaviour among Chinese adolescents - Xueyan Yang; Marcus W. Feldman (BMC, 2017)
Abstract Background A reversed gender pattern has been observed in the suicide rate in China compared to elsewhere. Like suicidal behaviour, non-suicidal self-injurious (NSSI) behaviour is a health-risk behaviour. We examined whether a reversed gender pattern existed in the prevalence of NSSI. Methods Online literature databases were searched for English and Chinese articles on NSSI behaviours among the Chinese. A meta-analysis with a random-effects model and a subgroup analysis were used to estimate the odds ratios of gender differences in NSSI prevalence among Chinese adolescents including college students, middle school students, and clinical samples, as well as rural, urban, and Hong Kong middle school students. Results There was a male bias in NSSI prevalence among college students (OR = 1.56, 95% CI = [1.30, 1.87], p < 0.001), and a female bias among middle school students (OR = 0.83, 95% CI = [0.73, 0.94], p < 0.01), but there was no gender difference among clinical samples (OR = 0.88, 95% CI = [0.41, 1.89], p > 0.1). The NSSI prevalence among middle school students had a female bias in the rural (OR = 0.58, 95% CI = [0.47, 0.72], p < 0.001) and Hong Kong areas (OR = 0.91, 95% CI = [0.86, 0.96], p < 0.001), with the gender difference in NSSI prevalence in the Hong Kong areas being greater than in rural areas. No gender difference in NSSI prevalence was found in urban areas (OR = 1.01, 95% CI = [0.84, 1.22], p > 0.1) among middle school students. Conclusions Our analysis indicated the existence of specific gender and age patterns in NSSI prevalence among Chinese adolescents. The sample type, age, and the areas that have different gender norms and culture could partly explain this pattern.